Assessment of Knowledge of Radiography Students about Personnel Radiation Monitoring Devices and Their Use - Prajapati, Jyoti; Kumar, Raushan; Boora, Navreet; Sah, Niraj K. (Indian Journal of Radiology and Imaging, 2022)
Background Personnel radiation monitoring equipment monitors the level of exposure to radiation and personnel will have to wear a personnel device for radiation detection while working. Personnel monitoring equipment is usually worn by a worker for 3 months.Aim This study aims to evaluate the knowledge of radiology students about personnel radiation monitoring devices and their use.Materials and Methods A questionnaire-based cross-sectional study was performed in the College of Paramedical Sciences, Teerthanker Mahaveer University, Delhi–Road Moradabad, Uttar Pradesh, India. This questionnaire-based study was performed for the period time of 1 year from June 2020 to May 2021. A validated questionnaire was circulated among undergraduate and postgraduate radiology students.Result In this study the questionnaire was filled by a total of 140 students who were pursuing bachelor's and master's degree programs, including 61% (86) males and 39% (54) females from the radiology department. According to the data master's knowledge levels are greater than the bachelor's level. The level of knowledge of monitoring devices among MRIT (M.Sc. in Radiology and Imaging Technology) second year (81%) is more than those of MRIT first year (80%), BRIT (B.Sc. in Radiology and Imaging Technology) third year (65%), and BRIT second year (66%).Conclusion It is concluded that there is a lack of awareness about personnel radiation monitoring systems. The level of knowledge of personnel radiation monitoring devices among students remains at a medium level from the results of our students as it has been concluded that master's knowledge level is greater than the bachelor's level. The level of knowledge of monitoring devices increases with the age of the students and the year completed.
Keywords: OSL; TLD; lithium fluoride